Microrredes no aprimoramento dos indicadores de continuidade de fornecimento em sistemas de distribuição de energia elétrica - Santos, Elton Rodrigo dos (2023)
The increasing integration of distributed generation (DG) units into the distributors' distribution system is a current reality. In a scenario in which the quality of service provision by distributors and the quality of the energy product are widely monitored by the National Electric Energy Agency (ANEEL) and by society, distributors are constantly looking for alternatives to improve their indicators. In view of this, islanded operation of generating units appears as a possibility to be evaluated. This is because, through the formation of microgrids, these distributed generation sources can guarantee the continuity of energy supply in the event of interruptions in the distributor's main source. Therefore, the DG units, when assuming the supply of energy to the connected consumer units of the system, bring benefits to the distributor and consumers both. Therefore, this dissertation seeks to analyze the implementation of islanded operations through microgrids and its impacts and improvements in continuity indicators. For this, a real distribution system belonging to the electrical energy distributor CERTAJA was selected. The technical data of the distribution network was extracted from the technical system in the format of the distributor's geographic database (BDGD) and subsequently modeled for simulation purposes. Next, the distributed generation capacity of the feeder was evaluated, in this case, a Small Hydroelectric Plant (PCH), connected to the permission holder's distribution system. Based on historical records, the PCH's ability to meet load demand was assessed. Subsequently, the degree of network segmentation was examined and the scope of four microgrids was defined. Next, steady-state power flow simulations were carried out using the OpenDSS software in Quasi-Static Time Series mode for a period of 24 hours. Through simulations, the operating condition in the formation of each microgrid was evaluated, analyzing the imbalance between phases, voltage transgression indices and power factor. Furthermore, historical data on supply interruptions in the feeder circuit was analyzed and it was verified that the islanded operation of microgrids results in a reduction in DEC and FEC indicators. Finally, a series of guidelines and measures were proposed to establish the operating agreement, operation programming routine and create operational procedures between the generation agent and the distributor.